Repair of the myometrial scar defect at repeat caesarean section: a modified surgical technique - Shahul Hameed Mohamed Siraj; Karuna Mary Lional; Kok Hian Tan; Ann Wright (BMC, 2021)
Abstract Background To investigate whether the existing surgical technique for uterine closure at repeat lower segment Caesarean section (LSCS) can be modified to achieve adequate residual myometrial thickness (RMT) to ensure scar integrity and reduce complications in future pregnancy. Methods Women with a significant scar defect at repeat LSCS had the anterior uterine wall closed by a single experienced obstetrician with a technique focused on recognition, mobilisation and apposition of the retracted myometrial edges at the boundary of the defect. This was aimed at anatomical restoration of the lower segment. The RMT at the scar area was assessed by postnatal pelvic ultrasound scan at three months. Results Thirty women with a history of at least one previous CS, incidentally found to have a large defect at operation underwent the technique with prior consent. A postnatal scan showed a mean residual myometrial thickness of 8.4 mm (SD ±1.3 mm; range 5.6-11.0 mm). The average operating time was 91 mins and the average blood loss 728 ml. Two women who underwent the repair have gone on to have a further uneventful CS. Conclusion This modified technique resulted in scan evidence of an RMT indicative of uterine wall stability postnatally and offers the potential for reducing the risk of rupture and placenta accreta spectrum (PAS) in future pregnancy.